A review on plant Cordia obliqua Willd. (Clammy cherry) - Gupta, Richa; Gupta, Ghanshyam Das (Pharmacognosy Reviews)
Cordia obliqua Willd. plant (Common name‑Clammy Cherry) belongs to family Boraginaceae. It is a medium‑sized deciduous tree and very vigorous in growth. According to traditional system, it possesses anthelmintic, purgative, diuretic, expectorant, antipyretic, hepatoprotective and analgesic action. The fruits are edible and used as pickle. The gum obtained from mucilage is used for pasting sheets of paper and as matrix forming material in tablet formulations. Phytochemical investigations show the presence of alkaloids, flavonoids, phenolics, tannins and reducing sugar. Evaluation of pharmacological activities confirmed C. obliqua plant as antimicrobial, hypotensive, respiratory stimulant, diuretic and anti‑inflammatory drug. A number of traditional activities of this plant still need scientific approval which will increase its medicinal potential. This review presents the Pharmacognostic properties, phytochemical constituents, traditional uses and biological activities reported for the plant and it will be helpful to explore the knowledge about Cordia obliqua Willd. for the researchers.
Keywords: Anti‑inflammatory; Boraginaceae; Clammy cherry; Cordia obliqua; pharmacological activities; phytoconstituents